INVESTIGATION OF BACTERIAL CONCRETE’S STRENGTH AND DURABILITY PROPERTIES - Sonali P. Patil1, Manik G. Deshmukh 2, Tejashri B. Lendave 3, Vaishnavi S. Bhosale3, PrajaktaS. Kale3, Nisha V. Mane3, MonaliA.Nagtilak3, Komal R. Ronge3, Pranita J. Jadhav3 (International Journal of Innovations in Engineering Research and Technology, 2022)
Concrete is the most recognized building material for its unfavorable strength and durability features. It has extremely high compressive strength and very weak in tension, owing of which reinforcing is employed in concrete to take the stress. As the concrete is brittle, it always results in the production of fractures in the stress zones upon loading and leads to the durability difficulties by limiting the life time of the buildings. To address such durability difficulties standard repair procedures like crack filling with epoxy injections and use of extra reinforcement for minimizing the crack width were in usage which entails a lot of economics. This lead to the invention of self-healing concrete idea employing some bacteria mixing in the concrete and the crack produced will be self-healed by bacteria as a consequence of reproduction of the bacteria. In the current study, it was explored to determine the strength and durability qualities of the M30 grade concrete by adding bacteria called Bacillus Subtilis as at varied percentages like 5ml, 10ml, 15ml and 20ml for 500ml of water to be combined in concrete. It was shown that at 10ml of bacteria for 500ml of water produces better strength qualities when compared with the standard concrete. As part of durability investigations, when the cubes are submerged in 5 percent H2SO4, at 10ml of bacteria it exhibiting the superior performance than the ordinary concrete.